The Hypothetical Learning Trajectory on Research in Mathematics Education Using Research-Based Learning - Prahmana, Rully Charitas Indra; Kusumah, Yaya S. (Pedagogika, 2016)
This study aims to create a learning trajectory on research in mathematics education using design research methodology to enhance research and academic writing skills for pre-service mathematics teachers. The fourteen pre-service mathematics teachers during 5 months period from one higher education institution in Tangerang – Indonesia was collected. The design research method was carried out in three phases: preliminary design phase, teaching experiments phase, and retrospective analysis phase. Initial data analysis of 14 pre-service teachers’ research and academic writing skills was conducted in six stages and the learning trajectories on this topic was identified. The fourteen pre-service teachers were divided into 7 groups and research independently to produce seven scientific articles. The six articles were published in the proceedings of Konferensi Nasional Matematika (National Congress of Mathematics) XVII 2014 and one article was published in the Elemen Journal Vol. 1 No. 1.